Primary ovarian hydatid cyst - Sachin A Badge; Maikal A Kujur; Avinash T Meshram; Anjalee G Ovhal (Medical Journal of Dr. D.Y. Patil University, 2016)
In humans, hydatid cyst is caused by Echinococcus granulosus. E. granulosus mainly affects the liver and lungs. It is very rare to get a primary ovarian hydatid cyst. Hence, we are reporting a very rare case of primary ovarian hydatid cyst.